DEVELOPMENT AND VALIDATION OF A STABILITY INDICATING RELATED SUBSTANCES OF ATENOLOL AND NITRENDIPINE BY RP-HPLC - ALUMURI, THULASEEDHAR; AMARABABU, NAMBURI L. A.; KURNOOL, ARAVİND; KANUPARTHY, PHANI RAJA; MERUGU, KARUNASREE (International Journal of Applied Pharmaceutics, 2022)
Objective: A validated stability-indicating RP-HPLC method for Atenolol and Nitrendipine was developed by separating its related impurities. Methods: By using Waters HPLC e-2695 quaternary pump with a PDA detector of 2998 instrument, the chromatographic separation of Atenolol, Nitrendipine and its related impurities was achieved on the column of Agilent eclipse C18 (150x4.6 mm, 3.5 µ) using gradient elution with a buffer containing 0.1percent formic acid and acetonitrile as a mobile phase with a flow rate of 1 ml/min at ambient temperature. A detector wavelength of 218 nm utilizing the PDA detector was given in the instrumental settings. The linearity was studied between the concentration range of 6.25-37.5 µg/ml of Atenolol, 0.75-4.5 µg/ml each of Atenolol imp-A, imp-B and 5-30 µg/ml of Nitrendipine, 0.5-3 µg/ml each of Nitrendipine imp-1, imp-2 were injected with a run time of 40 min. Validation of the proposed method was carried out according to an International Conference on Harmonization (ICH) guidelines. Results: LOD and LOQ for the Atenolol and its impurities were established with respect to test concentration. The plotted calibration curves were linear with a regression coefficient of R2>0.999, indicating that the linearity was with in the limit. As a part of method validation the parameters like specificity, linearity, accuracy, ruggedness, robustness were determined and the results were found to be within the allowable limit. Conclusion: The method developed was found to be applicable to routine analysis and to be used for the measurement of active pharmaceutical ingredients (i. e, Atenolol, Nitrendipine and their related impurities). Since there is no HPLC method reported in the literature for the estimation of Atenolol, Nitrendipine and their related impurities, there is a need to develop quantitative methods under different conditions to achieve improvement in specificity selectivity etc.